Relationship between Stress Levels And Students Resilience in Blended Learning Among Nursing Students at Citra Bangsa University During The COVID-19 Pandemic - Sico Elo, Fernando; Wawo, Balbina Antonelda Marled; Feoh, Fepyani Thresna (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
ABSTRACT Background: Quality learning is one aspect of improving the quality of education. Learning can occur offline (face-to-face) or online. When offline learning occurs simultaneously with online learning, stress arises for students due to numerous burdens and a denser schedule in navigating blended learning methods during this pandemic. Stress can interfere with student resilience. Resilience is the process, capacity, or outcome of individuals adapting successfully to challenges or threatening circumstances. This study aimed to analyze the relationship between stress levels and student resilience in managing combinations of blended offline and online learning methods during the COVID-19 pandemic at the UCB Nursing Study Program. The research method is quantitative, employing a correlational analytic research design with a cross-sectional approach. The sample consists of 153 respondents selected using the total sampling technique. Data will be collected by distributing questionnaires online through the Google Forms platform with informed consent and analyzed using the Chi-Square test. The results indicated a relationship between stress levels and student resilience in managing blended offline and online learning methods during the COVID-19 pandemic at the Nursing Study Program, Faculty of Health, University of Citra Bangsa, with a P-value of 0.001. Conclusion: Students can overcome psychological burdens in the form of stress in both online and offline learning, making this resilience crucial for helping students manage stress in their studies.